Let's solve your equation step-by-step.<span>17=<span><span>3<span>(<span>g+3</span>)</span></span>−g</span></span>
Step 1: Simplify both sides of the equation.<span>17=<span><span>3<span>(<span>g+3</span>)</span></span>−g</span></span><span>
Simplify: (Show steps)</span><span>17=<span><span>2g</span>+9</span></span>
Step 2: Flip the equation.<span><span><span>2g</span>+9</span>=17</span>
Step 3: Subtract 9 from both sides.<span><span><span><span>2g</span>+9</span>−9</span>=<span>17−9</span></span><span><span>2g</span>=8</span>
Step 4: Divide both sides by 2.<span><span><span>2g</span>2</span>=<span>82</span></span><span>g=4</span>
Answer:<span>g=<span>4</span></span>
Answer:
n = 3
Step-by-step explanation:
8n - (3n + 4) = 11
8n - 3n - 4 = 11
5n = 11 + 4
5n = 15
n = 3
What am I solving? Like what is the question?
Answer:
0.5
Step-by-step explanation:
22.7: 45.4 = 22.7/45.4
= 227/454
= 0.5